Analysis of The Influence Of Trust, Institutional Image, and Service Quality on Donator Loyalty with Satisfaction as a Moderating Variable (Case Study in LAZIS Muhammadiyah, Medan) - Ahmad Bayu Nugroho; Sri Sudiarti; Nur Ahmadi Bi Rahmani (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to determine and analyze the effect of trust, institutional image, and service quality on donor loyalty at LAZIS Muhammadiyah Medan with donor satisfaction as a moderating variable. The population of this research is regular donors from LAZIS Muhammadiyah Medan. The total sampling in this study is regular donors who donated at LAZIS Muhammadiyah Medan City in 2022 as many as 108 respondents. The method used in this study uses a quantitative approach using data from a questionnaire measured by a Likert scale. Testing the data in this study used multiple regression analysis, as well as the Moderated Regression Analysis (MRA) interaction test. The results of this study indicate that trust, institutional image, and service quality partially have a significant effect on donor loyalty. Interaction test results show that donor satisfaction does not moderate the effect of trust and service quality on donor loyalty. However, it moderates the effect of institutional image on donor loyalty satisfaction.